EFEKTIFITAS SUPLEMENTASI ZINC TERHADAP STATUS BIOKIMIA DAN ASUPAN ZAT GIZI ANAK BALITA PASCA PEMBERIAN VITAMIN A DOSIS TINGGI - Hendrayati Hendrayati; Satriyani Martha; Nursalim Nursalim (Media Gizi Pangan, 2020)
Abstrak  The incidence of stunting toddlers in Indonesia tends to increase, namely 35.6% in 2010 to 37.6% in 2013. In 2018 of stunting babies is still 36%.One form of nutrition services for toddlers in Indonesia is the provision of high doses of Vitamin A. This program can overcome the problem of  Xeropthalmia but has not helped much in overcoming stunting. Zinc supplementation is recommended supplementation for overcoming growth problems in children. Provision of high doses of vitamin A should be followed by zinc supplementation. The relationship between these two vitamins and minerals is closely related to the process of absorption of these two elements. In a state of vitamin A deficiency, there is a decrease in Zink-Binding Protein so that deficiency of vitamin A can cause disruption of zinc absorption. Zinc plays a role in the metabolism and transport of vitamin A and is needed in the synthesis of retinol transport protein (PTR), namely cellular hepatic PTR (cPTR) is an intracellular retinol transport protein in liver cells and PTR holo that carries retinol from the liver into the blood and other tissues.This study aims to determine the effect of zinc supplementation on stunting toddlers after the administration of high doses of vitamin A on nutrient intake and biochemical status. The design of the research was pre and post design, the research was carried out for one month, namely the administration of zinc syrup supplementation of 10 mg / day, at stunting children aged 2-4 years after administration of high doses of Vitamin A. Sample of 45 people. Indicators measured are energy intake, macro nutrient intake which includes carbohydrates, fats and proteins. Biochemical status such as zinc, albumin, total protein and hemoglobin.The results showed that the provision of zinc supplementation after administration of high doses of vitamin A in stunting toddlers was quite epective on biochemical status and not epective on energy intake and macro nutrients. Keywords  : Biochemical status , High doses of Vitamin A ,Nutrient intake, , Stunting,  Zinc